Die Herrschaft des Gesetzes: eine Untersuchung zum Verhältnis von politischer Theorie und Rechtssystem in der Konkurrenzgesellschaft - Neumann, Franz (Suhrkamp, 1980)
The thesis endeavours to show the interdependence of political theories, the social sub-structure, and the formal structure of the legal system in competitive society.